Mendidik Generasi Z: Tantangan dan Strategi di Era Digital - Rizki Heri Prasetyo; Masduki Asbari; Salsabila Amelia Putri (Journal of Information Systems and Management (JISMA), 2024)
This journal aims to explore effective methods in educating children in the current digital era, often referred to as "Kids Jaman Now." The objective of this research is to investigate the impact of technology use on the cognitive, social, and emotional development of children, and to identify educational strategies that support holistic growth in this context. Research methods involve literature analysis, surveys, and case studies to understand learning preferences, challenges, and potential solutions. The results highlight the importance of a balanced approach between technology use and teacher-led social interaction. Additionally, education strategies involving parents and teachers in guiding children towards positive technology use have proven effective. Practical implications of these findings can aid in designing education programs responsive to the demands of the times, ensuring balanced development for children in this digital era.